Psychological support for the Canadian Olympic Boxing Team in meta-transitions through the National Team Program - Schinke, R. S.; Stambulova, N. B.; Trepanier, D.; Oghene, O. (International Journal of Sport and Exercise Psychology, 2015)
The Canadian Olympic Men's Boxing Team was once among the most successful contingents in the world in its sport discipline but then lost this prominent status. At present, Canada's Boxing Team has begun preparation for the 2016 Olympics with the "Own the Podium" (OTP) Program providing financial support to the National Boxing Team and targeted Olympic candidates expected to podium at the 2016 Olympic Games. The authors reveal in this paper the first step of the project "Psychological Support for the Canadian Olympic Boxing Team in Meta-Transitions through the National Team Program" aimed at planning for the boxers' progressions through the 2013-2016 Olympic cycle. Integral to this program, the athletes' progressions are supported through the development of a system of National Team Psychological Support Services (NT-PSS). Within this submission, the authors further develop a vision of the 2016 Olympic Games as a career transition and consider how the Canadian Men's Boxing Team's staff, located within a broader national sport system, proactively map six meta-transitions for the boxers throughout the 2013-2016 Olympic cycle and plan the NT-PSS' content accordingly. The forthcoming meta-transitions are seen as turns between the phases of progressing Olympic cycle: (A) entering the National Team Program, (B) entering major international tournaments, (C) Olympic qualification, (D) focused preparation for the Olympics, (E) to the Olympic podium, and (F) to the post-Games.